Health Systems Institutional Characteristics A Survey of 29 OECD Countries - Paris, Valérie (OECD Publishing, 2010)
In 2008, the OECD launched a survey to collect information on the health systems characteristics of member countries. This paper presents the informaton provided by 29 of these countries in 2009. It describes country-specific arrangements to organise the population coverage against health risks and the financing of health spending. It depicts the organisation of health care delivery, focusing on the public/private mix of health care provision, provider payment schemes, user choice and competition among providers, as well as the regulation of heallth care suppply and prices. Finally, this document provides information on governnance and resource allocation in health systems (decentralisation in decisionmaking, nature of budget constraints and priority setting)
Keywords: Social Issues/Migration/Health